Antibacterial activity of several Malaysian leaves extracts on the spoilage bacteria of yellow alkaline noodles - Rosyid, Teza Alfindo; Karim, Roselina; Mohd Adzahan, Noranizan; Mohamad Ghazali, Farinazleen (Academic Journals, 2011)
Yellow alkaline noodle (YAN) is very susceptible to spoilage and has a short shelf life due to the high moisture content. This study was conducted to isolate and identify spoilage bacteria of YAN in an attempt to apply local plant extracts that possess antibacterial activity in extending the shelf life of YAN. Thirty colonies were isolated from spoiled YAN and were identified using the Biolog GEN III system. Eight bacteria which consisted of five Gram-positive (GP) and three Gram-negative (GN) (Bacillus pumilus, Clavibacter agropyri, Corynebacterium urealyticum, Corynebacterium jeikeium, Enterobacter cloaceae, Pseudomonas aeruginosa, Serratia marcescens and Staphylococcus sciuri) were identified. E. cloaceae and S. sciuri were the most abundant bacteria on YAN with percentage values of 23 and 26%, respectively. The antibacterial activities of ethanol and water extracts of six types of leaves (Centella asiatica, Jasminum sambac, Pereskia bleo, Cosmos caudatus caudatus, Murraya koenigii, and Melicope lunu) against all the identified bacteria were studied. The ethanol extracts of M. koenigii are most effective extract that possess the highest antibacterial activity against all the eight spoilage bacteria studied.